2021
DOI: 10.1155/2021/6545728
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Talk between Oxidative Stress and m6A RNA Methylation in Cancer

Abstract: Oxidative stress is a state of imbalance between oxidation and antioxidation. Excessive ROS levels are an important factor in tumor development. Damage stimulation and excessive activation of oncogenes cause elevated ROS production in cancer, accompanied by an increase in the antioxidant capacity to retain redox homeostasis in tumor cells at an increased level. Although moderate concentrations of ROS produced in cancer cells contribute to maintaining cell survival and cancer progression, massive ROS accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 333 publications
0
27
0
Order By: Relevance
“…Cancer cells with aberrant oxidative and antioxidant systems often exhibit dynamic crosstalks between oxidative stress and m 6 A modifications where intracellular ROS levels can change the levels of m 6 A methylation but may also be regulated by m 6 A modifications [866]. An analysis of RNA-seq assays for mouse neuroblastoma (Neuro-2A) cells treated with paraquat (PQ)-an oxidative stress-inducing herbicide-revealed that both oxidative stress as well as antioxidative stress can generate distinct transcriptome distributions of m 6 A peaks that modified circular RNAs (circRNAs) in treated cells, where PQ-treated cells presented abundant m 6 A peaks across the CDS region but exhibited less peaks in the 3′-UTR region; whereas cells pretreated with the antioxidant N-acetylcysteine (NAC) demonstrated the exact opposite effect.…”
Section: Melatonin Modulates the Expression Of M 6 A Mettl3 Methyltra...mentioning
confidence: 99%
“…Cancer cells with aberrant oxidative and antioxidant systems often exhibit dynamic crosstalks between oxidative stress and m 6 A modifications where intracellular ROS levels can change the levels of m 6 A methylation but may also be regulated by m 6 A modifications [866]. An analysis of RNA-seq assays for mouse neuroblastoma (Neuro-2A) cells treated with paraquat (PQ)-an oxidative stress-inducing herbicide-revealed that both oxidative stress as well as antioxidative stress can generate distinct transcriptome distributions of m 6 A peaks that modified circular RNAs (circRNAs) in treated cells, where PQ-treated cells presented abundant m 6 A peaks across the CDS region but exhibited less peaks in the 3′-UTR region; whereas cells pretreated with the antioxidant N-acetylcysteine (NAC) demonstrated the exact opposite effect.…”
Section: Melatonin Modulates the Expression Of M 6 A Mettl3 Methyltra...mentioning
confidence: 99%
“…The involvement of m6A modification in redox homeostasis is evidenced by the following findings. The level of m6A methylation is increased globally in response to oxidative stress [170,171]. Hypoxic preconditioning treatment-induced protection of myoblast heart cells (H9c2) from H 2 O 2 is associated with a significant increase in the total level of m6A methylation and METTL3 expression [170]; however, inhibition of m6A methylation attenuates the protection [170].…”
Section: M6a Modification and Oxidative Stress Damage In The Eyementioning
confidence: 99%
“…Hypoxic preconditioning treatment-induced protection of myoblast heart cells (H9c2) from H 2 O 2 is associated with a significant increase in the total level of m6A methylation and METTL3 expression [170]; however, inhibition of m6A methylation attenuates the protection [170]. Additional studies have shown that kidney injury and dysfunction induced by excess ROS production are regulated by m6A RNA methylation [171,172].…”
Section: M6a Modification and Oxidative Stress Damage In The Eyementioning
confidence: 99%
See 2 more Smart Citations